Targeted cryoprecipitate transfusion in severe traumatic haemorrhage. Issue 9 (September 2020) - Ho, Debbie; Chan, Erick; Campbell, Don; Wake, Elizabeth; Walters, Kerin; Bulmer, Andrew C.; McCullough, James; Wullschleger, Martin; Winearls, James
Abstract: Background: Severe traumatic haemorrhage is the leading cause of death in young adults. Trauma Induced Coagulopathy is a complex and multifactorial phenomenon associated with severe traumatic haemorrhage. Fibrinogen is one of the first coagulation factors to become depleted in TIC and evidence suggests that severely injured trauma patients with hypofibrinogenaemia have poor outcomes. It is postulated that early fibrinogen replacement can improve clinical outcomes. This study investigated cryoprecipitate transfusion in hyopfibrinogeneamic trauma patients. Methods: This retrospective, single center, observational study investigated the use of cryoprecipitate in severely injured trauma patients admitted to an Australian Level I Trauma Centre. The primary outcome was time to administration of cryoprecipitate after identification of hypofibrinogenaemia using ROTEM (FIBTEM A5). Data collected included demographics, ISS, laboratory values of coagulation and blood product usage. Results: 71 patients received cryoprecipitate with a median time of 61 minutes [IQR 37-93] from FIBTEM A5 result to initial cryoprecipitate administration. At 24 hours following admission to ED, Clauss Fibrinogen levels increased by 1.30g/L [IQR 0.45-1.85] and FIBTEM A5 assay increased by 8mm [IQR 3.0-11.3]. Changes in both variables were highly significant (p<0.001) and Clauss Fibrinogen versus FIBTEM A5 values showed moderate to strong correlation (R=0.75-0.80). Conclusion: This study demonstrated that early administration of cryoprecipitate was both feasible and efficacious in fibrinogen replacement in severe traumatic haemorrhage. High-level evidence supporting cryoprecipitate or fibrinogen concentrate replacement with regards to efficacy and feasibility is required to guide future clinical practice. This study provided baseline data to inform the design of further clinical trials investigating fibrinogen replacement in traumatic haemorrhage.